Long-term outcomes in non-CAH 46,XX DSD - Grouthier, Virginie; Bachelot, Anne (Frontiers in Endocrinology, 2024)
Differences/disorders of sex development (DSD) comprise a large group of rare congenital conditions. 46,XX DSD, excluding congenital adrenal hyperplasia (CAH), represent only a small number of these diseases. Due to the rarity of non-CAH 46,XX DSD, data on this sex chromosomal aberration were confined to case reports or case series with small numbers of patients. As the literature is still relatively sparse, medical data on the long-term effects of these pathologies remain scarce. In this review, we aim to provide an overview of current data on the long-term follow-up of patients with non-CAH 46,XX DSD, by covering the following topics: quality of life, gender identity, fertility and sexuality, global health, bone and cardiometabolic effects, cancer risk, and mortality. As non-CAH 46,XX DSD is a very rare condition, we have no accurate data on adult QoL assessment for these patients. Various factors may contribute to a legitimate questioning about their gender identity, which may differ from their sex assigned at birth. A significant proportion of gender dysphoria has been reported in various series of 46,XX DSD patients. However, it is difficult to give an accurate prevalence of gender dysphoria and gender reassignment in non-CAH 46,XX DSD because of the rarity of the data. Whatever the aetiology of non-CAH 46,XX DSD, fertility seems to be impaired. On the other hand, sexuality appears preserved in 46,XX men, whereas it is impaired in women with MRKH syndrome before treatment. Although there is still a paucity of data on general health, bone and cardiometabolic effects, and mortality, it would appear that the 46,XX DSD condition is less severely affected than other DSD conditions. Further structured and continued multi-center follow-up is needed to provide more information on the long-term outcome of this very rare non-CAH 46,XX DSD condition.